Cambodia Rice Sector Review : Turning Cambodian Rice into White Gold - World Bank Group (World Bank, Washington, DC, 2015)
Cambodia’s rice harvests have been rising significantly since 2005, powered by improved and expanded irrigation and attractive farm gate prices. In 2010, the Cambodian government announced an export target of 1.0 million tons of milled rice by 2015. This analysis, which updates reports prepared in 2009 and 2011, seeks to identify short-term policy measures that can assist Cambodian exporters in boosting exports in the near term. This report examines new and expected investments in the larger rice mills and polishing factories, export trends, recent changes in milling costs, and provides a look at logistical costs and some alternatives. Additionally, import trends are examined in two current markets - the European Union (EU) and Russia, and in three other key markets - Indonesia, the Philippines, and China. Finally, an analysis is provided of the current Thai rice policy which impacts on local prices and investment interests by Thai rice exporters.